Exposure to proton pump inhibitors and risk of pancreatic cancer: a meta-analysis. Issue 3 (3rd March 2020) - Alkhushaym, Nasser; Almutairi, Abdulaali R.; Althagafi, Abdulhamid; Fallatah, Saad B.; Oh, Mok; Martin, Jennifer R.; Babiker, Hani M.; McBride, Ali; Abraham, Ivo
ABSTRACT: Objectives : To estimate the pancreatic cancer risk among subjects exposed versus not exposed to proton pump inhibitors. Methods : The authors searched PubMed, EMBASE, Scopus, Cochrane Library, and clinicaltrials.gov to identify relevant studies. The authors quantified pancreatic cancer risk among subjects exposed versus not exposed to PPIs, expressed as the pooled (adjusted) odds ratio (OR/aOR) and 95% confidence interval (95%CI) in overall and sensitivity analyses. Results : One randomized trial, two cohort, four case-control, and five nested case-control studies with 700, 178 subjects (73, 985 cases; 626, 193 controls) were retained. PPI exposure was associated with pancreatic cancer risk (OR = 1.75, 95%CI = 1.12–2.72, I 2  = 99%); confirmed in sensitivity analyses for high-quality studies, observational studies, case-control studies, studies with pancreatic cancer as the primary outcome, and in sensitivity analyses for diabetes and obesity but not for pancreatitis and smoking. This association was independent of the duration and Defined Daily Dose of PPI exposure. Rabeprazole had a singular significant association with pancreatic cancer (OR = 5.40, 95%CI = 1.98–14.703, I 2  = 87.9%). Conclusion : The class of PPIs is associated with a 1.75-fold increase in pancreatic cancer risk, confirmed in sensitivity analyses.